Pengaruh Suhu dan Waktu Pengeringan Terhadap Karakteristik Teh Herbal Daun Matoa (Pometia pinnata J.R. Forst. & G. Forst.) - Samosir, Melania Veronika; Yusasrini, Ni Luh Ari; Mayun Permana, I Dewa Gde (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 1 (2024): Jurnal ITEPADO - 10.24843/itepa.2024.v13.i01.p03, 2024)
Herbal tea is an efficacious herbal drink that is generally made from one or several ingredients made from dried leaves, seeds, wood, fruit, flowers, apart from the tea plant (Camellia sinensis). One of the plants that can be used as herbal tea is matoa leaves (Pometia pinnata). There are important stages in herbal tea processing that can affect the quality of herbal teas, namely drying which includes temperature and drying time. This study aimed to determine the effect of temperature and drying time on the characteristics of matoa leaf herbal tea and to obtain the right temperature and drying time that can produce matoa leaf herbal tea with the best characteristics. The experimental design used in this study was a factorial Complete Randomized Design (CRD) with 2 factors consisting of 3 levels each. The first factor is the drying time (W1 = 1 hour, W2 = 2 hours, W3 = 3 hours). The second factor of drying temperature (T1= 50oC, T2= 60oC, T3=70oC). The above treatments were repeated 2 times so that 18 experimental units were obtained. Analysis of variance was used to assess the data that were acquired and if the treatment had a noticeable effect, it was continued with the Duncan Multiple Range Test (DMRT). The results showed that the interaction of temperature and drying time had a significant effect on water content, extract content in water, total phenols, tannin content and antioxidant levels of herbal tea matoa leaves. Temperature and drying time had a significant effect on ash content, total flavonoids, taste (based on scoring and hedonic tests) and overall acceptance of herbal tea matoa leaves. The best treatment was obtained at drying with a temperature of 70oC and drying time of 3 hours with a characteristic moisture content of 5.10%, ash content of 6.29%, water extract content of 76.04%, total phenols content of 108.36 mgGAE/g, total flavonoids content of 9.52 mgQE/g, tannin content of 0.67 mgTAE/g, antioxidant content of 78.03%, neutral color, neutral aroma, dislike taste with bitter taste score, and neutral overall approval. Keywords: drying temperature, drying time, herbal tea, matoa leaf